Cu(II) Complexes of New Sulfa Drug Schiff Base Ligands: Synthesis, Structural Characterization, Antimicrobial Activities, and Time-Killing Kinetics - Sahal, Hakan; Idil, Onder; Canpolat, Erdal; Ozkan, Mustafa (Maik Nauka/Interperiodica/Springer, 2023)
Synthesis of three different new sulfonamide compounds (L-1-L-3) and their Cu(II) complexes were carried out. Their structures were characterized by spectroscopic methods such as Fourier transform infrared, Proton nuclear magnetic resonance and elemental analysis. Cu(II) complexes were screened for Gram-positive, Gram-negative bacteria and against yeast using the microdilution method. In particular, CuL2 was found to have significant antimicrobial effects on Gram (-), Gram (+) and eukaryotic yeast. The results showed that CuL2 exhibited better antimicrobial activity than other complexes. Depending on the antimicrobial activity results, time killing experiments of CuL2, the most effective complex, were performed.
Keywords: sulfa drug; Schiff base; Cu(II) complex; antimicrobial activity; time killing